Respuesta :

Answer:

As x gets smaller, pointing to negative infinity, the value of p increases, pointing to positive infinity.

As x increases, pointing to positive infinity, the value of p increases, pointing to positive infinity.

Step-by-step explanation:

To find the end behaviour of a function f(x), we calculate these following limits:

[tex]\lim_{x \to +\infty} f(x)[/tex]

And

[tex]\lim_{x \to -\infty} f(x)[/tex]

At negative infinity:

[tex]\lim_{x \to -\infty} (4x^{8} - 6x^{7} + 3x^{3} - 10)[/tex]

When the variable points to infinity, we only consider the term with the highest exponent. So

[tex]\lim_{x \to -\infty} (4x^{8} - 6x^{7} + 3x^{3} - 10) = \lim_{x \to -\infty} 4x^{8} = 4*(-\infty)^{8} = \infty[/tex]

Plus infinity, because the exponent is even.

So as x gets smaller, pointing to negative infinity, the value of p increases, pointing to positive infinity.

At positive infinity:

[tex]\lim_{x \to \infty} (4x^{8} - 6x^{7} + 3x^{3} - 10) = \lim_{x \to \infty} 4x^{8} = 4*(\infty)^{8} = \infty[/tex]

As x increases, pointing to positive infinity, the value of p increases, pointing to positive infinity.

Answer:

A - As x -> infinity, p(x) -> infinity, and as x -> -infinity, p(x) -> infinity.

Step-by-step explanation: